Literature Study on the Influence of Parenting Styles as a Critical Challenge for Early Childhood Education Teachers - Titik Rokayani; Dwi Anggi; Sri Katoningsih; Monique Sénéchal (HADHANATUNA: Journal of Early Childhood Education, 2026)
Parenting styles play an important role in determining the quality of early childhood development, making them a crucial topic of study for early childhood education teachers in understanding the dynamics of learning that occur in schools. This study aims to examine the influence of various parenting styles on child development and to identify the challenges faced by early childhood education teachers in aligning education at home and at school. This research employs a systematic literature review method by analyzing relevant scholarly articles related to parenting styles, social-emotional development, character development, and parent–teacher collaboration. The findings indicate that democratic and supportive parenting styles contribute positively to children’s social-emotional development and character formation, while authoritarian and permissive parenting styles tend to cause behavioral problems and difficulties in adapting to early childhood education environments. The discussion emphasizes that harmonious collaboration between parents and teachers is essential to create a consistent learning environment that supports the optimal development of young children.